Transformation of Islamic Education to Build Religious-Humanistic Character - Arfik Muji Rahayu (Jurnal Pendidikan Profesi Guru, 2023)
The phenomena caused by progress and modernization are very diverse, including the rise of behavior and attitudes that appear in various layers of society that are far from the values of Islamic teachings. Various cases milling about before our eyes and often heard in our ears, have occurred among teenagers and even by adults. Disrespectful behavior, immorality, arrogance, arrogance, discrimination, bullying, violent behavior, extremism and so on can be seen. Even then the perpetrators are very diverse and are carried out by various groups, both students, workers, the unemployed, the lower, middle and elite class or even those who are educated and have a position. This is a phenomenon that we often see and find as a result of the progress and modernization of today's digital age. With this fact, education in Indonesia is very urgent to get more serious attention, where character building is so important for humans, especially for students in madrasas/schools, Islamic boarding schools and even Islamic education in the community. Therefore, every stakeholder and policy maker must be able to work hard together in responding and addressing such conditions. One of the efforts is how to find an educational formula that is oriented toward the realization of human beings who have religious-humanistic characters or have good social religiosity, especially the importance of transforming the concept of Islamic education towards the formation of Islamic and humane characters. Thus, efforts to shape religious-humanistic human characters through the transformation of Islamic education are very urgent to implement. Furthermore, what are the steps that must be taken by an educator in the process of Islamic Education in order to produce output of students with good character and social religiosity? This research method uses literature research. Problems are discussed through a literature study. Religious and humanistic character values possessed by students are believed to be able to lead to the educational process towards a balanced relationship between humans and Allah (hablun min Allah) and also the relationship between humans and each other (hablun min al-nas).